Analisis Keefektivitasan Pemanfaatan E-Learning Sebagai Media Pembelajaran Pendidikan Agama Islam Pada Masa Pandemi Corona (Covid-19) - Yeni Yuliana (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
Abstract The internet can be made as a way to transfer knowledge from lecturers to students, while Learning that utilizes the internet is one of the E-Learning Learning media. E-learning is distance learning that utilizes computer technology or computer networks or the Internet E-learning, so that it can enable the learning process through computers in their respective places without having to physically go to attend classes or lectures in class, Systems e-learning learning is a new way of teaching and learning. E-learning as a special learning media PAI courses provide a very important role and a large function in the course because so far there are many shortcomings and weaknesses such as the limitations of space and time in the teaching and learning process through E-learning which prioritizes the efficiency of learning so students get full teaching even though they do not have to be face to face, can also be accessed anywhere, anytime, according to the assignments given by the lecturer usually scheduled with a specified deadline. The development of education towards e-learning is a must so that the quality standards of education can be improved, E-learning is one of the uses of internet technology in the delivery of learning and its broad reach. E-learning can also be an answer to a health problem that is Pandemic Corona (Covid-19) which is very influential also in every aspect of life, especially in education.Keywords: Effectiveness, Utilization, Islamic Religious Education, E-Learning, Covid 19. Abstrak Internet dapat dijadikan cara untuk mentransfer ilmu pengetahuan dari Dosen kepada mahasiswa/mahasiswi. Adapun Pembelajaran yang memanfaatkan internet salah satunya adalah media pembelajaran E-Learning. E-learning adalah pembelajaran jarak jauh (distance learning) yang memanfaatkan teknologi komputer atau jaringan komputer atau internet E-learning, sehingga dapat memungkinkan proses pembelajaran melalui komputer di tempat mereka masing– masing tanpa harus secara fisik pergi mengikuti pelajaran atau pun perkuliahan di kelas, Sistem pembelajaran e-learning adalah cara baru dalam proses belajar mengajar. E-learning sebagai media pembelajaran khususnya mata kuliah PAI memberikan peran sangat penting dan fungsi yang besar pada mata kuliah tersebut karena selama ini terdapat banyak kekurangan dan kelemahan seperti keterbatasan ruang dan waktu dalam proses belajar mengajar melalui E-learning yang mengedepankan keefisienan dalam belajar sehingga mahasiswa mendapat pengajaran yang penuh meski tidak harus bertatap muka, juga bisa di akses di mana saja, kapan saja, sesuai dengan tugas yang diberikan oleh dosen biasanya terjadwal dengan batas waktu yang di tentukan. Pengembangan pendidikan menuju e-learning merupakan suatu keharusan agar standar mutu pendidikan dapat ditingkatkan, E-learning merupakan salah satu penggunaan teknologi internet dalam penyampaian pembelajaran serta jangkauannya yang luas. E-learning juga dapat menjadi jawaban dari suatu permasalahan kesehatan yaitu Pandemi Corona (Covid-19) ini yang sangat berpengaruh juga pada setiap aspek kehidupan terutama bidang pendidikan.Kata kunci : Keefektifitas, Pemanfaatan, Pendidikan Agama Islam, E-Learning, Covid 19.